Pengembangan Sistem Informasi Pengajuan ISBN di Perpustakaan Politeknik Caltex Riau - dini hidayatul qudsi; Mutia Sari Zulvi (Jurnal Komputer Terapan, 2023)
The ISBN (International Standard Book Number) application is one of the facilities provided by the Riau Caltex Polytechnic Library (PCR) to the academic community to assist the academic community to get ISBNs from the National Library. Until now, the ISBN application process for the Caltex Riau Polytechnic Publisher (PCR) has taken quite a long time. The author communicates via email sent to library staff, causing the author and staff have difficulty seeing the progress status of the ISBN application. Therefore, a library system was built to manage the ISBN management process for the Caltex Polytechnic Publisher. The system development uses Rapid Application Development (RAD) methodology. The development of the website using the RAD methodology requires a strong commitment between developers and users, so that the system can be completed within the specified time. The resulting system has been tested using the Black Box testing method and states that the system features are 100% running as expected.